Análise econômica das políticas de incentivos à cultura no Brasil - Cavalcanti, Gabriel Estellita Lins (2006)
Brazil offers investor a legislation that places it between the best countries, if not the best one, where to develop arts related projects 1. At least in theory. This work has as objective to tread the path of the incentive laws in Brazil, from the beginning, with the Sarney Law, until the Rouanet Law2, including an analysis of local incentive laws, which were created as a response for process discontinuities. The Brazilian arts market shows some strong externalities3, and that is probably the reason why its impossibilities for it to meet equilibrium. Therefore, is necessary a governmental intervention. Brazilian arts politics uses, as the most important instrument, tax deduction as a benefit to attract the private capital. Partnerships are drawn with private companies, which become responsible for sponsoring the projects selected by the Culture Ministry. As a payback, they are allowed to deduct, integrally or partially, this amount from taxes. But this is a very malformed contract, which brings losses for society. Government takes up the entire risk, opening windows for some serious risks of Moral Hazard4. Besides, due to the deep differences among artists, art sectors and their access for private capital, this model ends up raising problems of Adverse Selection5. For a better comparison and analysis of the Brazilian arts politics, four international cases were listed - United States, England, Portugal and Spain. Taking into account the previously raised critics and analyses, it will be suggested alternatives for the contract model adopted by the government and alternative ways of financing arts. Therefore, the Government may assure a better return for society, without missing its important role of fomenting the cultural market, balancing its externalities.